Gone for good? Subsidies with export share requirements in China: 2002–13 - Defever, Fabrice; Riaño, Alejandro (Oxford University Press, 2015)
This paper presents a simple model of subsidies with export share requirements (ESR) in a heterogeneous firm environment. A two-country general equilibrium version of the model with a single 100% ESR is calibrated using firm-level data from the 2002 wave of the Business Environment and Enterprise Performance Survey collected by the World Bank for China. The calibrated model is used to gauge the change in subsidies with ESR that is consistent with the fall in the share of ‘pure exporters’, firms exporting all their output, observed in China, from 25.7% in 2002 to 11.1% in 2013. Our results indicate that a 6.9% reduction in the ad-valorem subsidy rate available to firms that export all their output is consistent with the observed fall in their share of exporting firms. Expenditure in subsidies (as a share of value-added) falls by 66% and welfare in China increases by 1.76% while real income in the rest of the world falls by 0.59%.